The Effectiveness of Problem Based Learning assisted by Educaplay on Pancasila Education Learning Outcomes of Elementary School Students - Aulli Qzara Ainun Nisa Mufi Dayanti; Kurotul Aeni; Daniyal Manzoor Khan (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractLearning models that do not actively involve students in the learning process are one of the factors causing low learning outcomes. This research aims to test and analyze how effective the problem-based learning model, which utilizes Educaplay media, is on student learning outcomes. The method used by researchers is a quasi-experimental design with a nonequivalent control group. The subjects of this study were 85 fifth-grade students of Jatisari state elementary School, Semarang City, Indonesia i.e. 28 students of class VB as the experimental class, and 28 students of class VC as the control class. Learning outcomes data were obtained from test techniques and non-test techniques. Data analysis used SPSS 25, consisting of normality, homogeneity, t-test, and N-Gain tests. The results indicated that the significant value in the independent t-test was 0.000 < 0.05, so Ha was accepted and H0 was rejected. This data indicates a significant difference in the learning outcomes between the students in the experimental and control classes. N-Gain percent was 66% (moderately effective) in the experimental class and 39% (ineffective) in the control class. This study indicates that the application of the PBL model based on Educaplay media is effective in improving student learning outcomes.Keywords: educaplay, effectiveness, learning outcomes, PBL, pancasila education. AbstrakModel pembelajaran yang kurang melibatkan siswa secara aktif dalam proses pembelajaran menjadi salah satu faktor penyebab rendahnya hasil belajar. Penelitian ini bertujuan untuk menguji dan menganalisis seberapa efektif model pembelajaran berbasis masalah yang memanfaatkan media Educaplay terhadap hasil belajar siswa. Metode yang digunakan peneliti adalah quasi eksperimen dengan desain nonequivalent control group design. Subjek penelitian ini adalah siswa kelas V SD Negeri Jatisari sebanyak 85 orang, yaitu kelas VB sebanyak 28 orang sebagai kelas eksperimen, dan kelas VC sebanyak 28 orang sebagai kelas kontrol. Data hasil belajar diperoleh dari teknik tes dan teknik non tes. Analisis data menggunakan SPSS 25 yang terdiri dari uji normalitas, homogenitas, uji t, dan uji N-Gain. Hasil penelitian menunjukkan bahwa nilai signifikansi pada uji t independen sebesar 0,000 < 0,05, sehingga Ha diterima dan H0 ditolak. Data ini menunjukkan adanya perbedaan hasil belajar yang signifikan antara siswa kelas eksperimen dan kelas kontrol. Persentase N-Gain adalah 66% (cukup efektif) di kelas eksperimen dan 39% (tidak efektif) di kelas kontrol. Penelitian ini menunjukkan bahwa penerapan model PBL berbasis media Educaplay efektif dalam meningkatkan hasil belajar siswa.Kata kunci: educaplay, keefektivan, hasil belajar, PBL, pendidikan pancasila.